Common eider data for Harms et al MS: Feather corticosterone reveals effect of moulting conditions in an Arctic migratory bird - Harms, N. Jane; Legagneux, Pierre; Gilchrist, H. Grant; Bêty, Joël; Love, Oliver P.; Forbes, Mark R.; Bortolotti, Gary R.; Soos, Catherine (Dryad Digital Repository, 2014)
These data were collected from the field from 2007-2011. Column headings are as follows: ID (year plus bird band number); Band (bird band number); year (year eider was captured); CORTf (feather corticosterone in pg/mm); arrival (eider arrival date on breeding colony in Julian days); relArrival (relative arrival date); mass (eider mass in grams); Lay (date first egg was laid); relLay (relative lay date); nest (at least one egg was successfully hatched); Survival (1=eider found dead by end of breeding season, 0= eider that was not found dead during breeding season)